Effects of enzymatic activation of bleaching gels on hydrogen peroxide degradation rates, bleaching effectiveness, and cytotoxicity - Zuta, Uxua Ortecho [UNESP]; De Oliveira Duque, Carla Caroline [UNESP]; De Alencar E Silva Leite, Maria Luísa [UNESP]; Bordini, Ester Alves Ferreira [UNESP]; Basso, Fernanda Gonçalves [UNESP]; Hebling, Josimeri [UNESP]; De Souza Costa, Carlos Alberto [UNESP]; Soares, Diana Gabriela (Operative Dentistry, 2019)
Objectives: The aim of this study was to evaluate the effect of horseradish peroxidase (HRP) on the release of free radicals, bleaching effectiveness, and indirect cytotoxicity of a 35% hydrogen peroxide (HP) bleaching gel. Methods and Materials: First, HP degradation rates and free radical release were evaluated for 35% HP in contact or not with HRP (10 mg/ mL). The bleaching gel associated or not with HRP was then applied (3 3 15 minutes) to enamel/dentin discs adapted to artificial pulp chambers, and the culture medium in contact with dentin surfaces (extract) was collected and exposed to cultured odontoblast-like cells. Membrane damage and viability of cells as well as oxidative stress were evaluated. Residual HP/free radical diffusion was quantified, and bleaching effectiveness (DE) was assessed. Unbleached discs served as negative controls. Results: The addition of HRP to the 35% HP bleaching gel enhanced the release of free radicals in comparison with plain HP gel. The 35% HP-mediated cytotoxicity significantly decreased with HRP in the bleaching gel and was associated with reduced HP/free radical diffusion through the enamel/dentin discs. DE values increased every bleaching session for HRP-containing gel relative to positive control, accelerating the whitening outcome. Conclusion: The enzymatic activation of a 35% HP bleaching gel with HRP accelerated HP degradation mediated by intensification of free radical release. This effect optimized whitening outcome as well as minimized residual HP and free radical diffusion through enamel and dentin, decreasing the harmful effects on odontoblast-like cells.